(untitled) (Revista Venezolana de Salud Pública, 2018)
The complex of organisms that inhabit the intestine and which includes a large number of bacteria, fungi, yeasts, viruses and phage is known as Intestinal Microbiota (MI). The balance between the MI, the epithelial barrier and the local immune system determines intestinal homeostasis in the healthy subject. MI is important in regulating the rescue and energy expenditure, as well as in fat storage and food intake in the host. Due to the increasing impact of metabolic disorders in society, the need to compile, summarize and analyze the most relevant bibliography on recent advances in the understanding of the intestinal microbiota and its possible relationship with these disorders. Investigations with experimental rodent models suggest that the bacterial composition, functional genes and metabolic activities of IM are altered in subjects with obesity, metabolic syndrome or type 2 diabetes (DT2). In addition, it appears that dietary fat is also an important factor affecting the composition of MI, as well as the barrier function of the intestine and therefore, plasma levels of LPS, producing a metabolic endotoxemia that could contribute to the development low-grade systemic inflammation, insulin resistance and DT2. Finally, recent research in rodents indicates that there is a relationship between MI and the pathogenesis of obesity, metabolic syndrome and even DT2.